Geographical variation in fecundity and reproductive investment of Loxopagurus loxochelis (Decapoda: Anomura: Diogenidae) along the south-eastern coast of Brazil - Stanski, Gilson; Hippolito, Alicia Giolo; Costa, Rogerio C. [UNESP]; Castilho, Antonio L. (Taylor & Francis Ltd, 2019)
We aimed to study the fecundity and reproductive investment of Loxopagurus loxochelis under different environmental conditions. In total, 67 ovigerous females were analyzed, 20 from Macae, 26 from Ubatuba and 21 from Cananeia. The cephalothoracic shield length, fecundity and reproductive investment (Ubatuba 10.2%, Macae 8.9% and Cananeia 7.5%) were different among the regions (ANCOVA, p < 0.05), caused by different abiotic resources and environmental characteristics found in each sampling region. Cananeia had the smallest individuals and low availability of adequate shells to hermit crabs, a condition that may have affected the growth and reproduction of the animals. Macae has a continuous transport of nutrients such as nitrogen and phosphorus to the surface promoted by the Cabo Frio Upwelling zone, which may be a favourable condition for plankton production and, consequently, the extended 'match/mismatch' adjustment of spawning females of L. loxochelis. We propose that the highest reproductive investment on the Ubatuba coast is a consequence of regional environmental scenarios of waters colder than the Cananeia region, i.e. females concentrate more energy to reproduce seasonally. Thus, we proved that patterns of L. loxochelis' reproduction can change on a regional scale according to the local condition of shell supply and water temperature.
Keywords: Bycatch; trawling; Anomura; ecology